Legal Perspectives on Leadership Transformation and Workforce Flexibility in Police Institutions: State and Islamic Law in the Digital Era - Tinto Adi Nugraha; Nuri Herachwati; Fiona Niska Dinda Nadia; Prayogo, Fatma Merve (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
Leadership transformation and workforce flexibility in police institutions have become crucial issues in the rapidly evolving digital era. This article examines the legal perspectives on leadership changes and workforce adaptation in police institutions based on state law and Islamic law. Using a normative juridical approach, this study explores how modern regulations and Islamic legal principles support leadership reform and workforce flexibility to enhance police effectiveness and professionalism. The findings indicate that state law provides a dynamic regulatory framework to support leadership transformation and workforce flexibility, while Islamic law offers ethical and justice-based leadership principles that strengthen institutional integrity. The implications of this study highlight the importance of synergy between state law and Islamic law in formulating police policies that are responsive to digitalization challenges and social changes. Thus, this study underscores that technology-based leadership transformation and workforce flexibility, when supported by clear regulations and strong legal principles, can enhance the professionalism and effectiveness of police institutions in carrying out their duties in the digital era.